Celebrity endorsement using different types of new media and advertising formats - Uribe, Rodrigo; Buzeta, Cristian; Manzur, Enrique; Celis, Martina (Academia (Consejo Latinoamericano de Escuelas de Administración), 2022)
Purpose>This study aims to examine the effectiveness (ad attitude, brand attitude and purchase intention) of celebrity endorsement in the form of explicit vs embedded advertising in the context of different new media (digital and social media).Design/methodology/approach>An online experiment was conducted using a 2 (digital media vs social media) × 2 (explicit vs embedded celebrity endorsement) between-subjects design. Participants (n = 137) were exposed to a fictitious piece of online branded content using celebrity endorsement. Four experimental treatments were generated as the authors manipulated the new media and the explicitness of the celebrity endorsement in the ad piece.Findings>The main result highlights that using social media (vs digital media) enhances celebrity endorsement's indirect influence on purchase intention via the serial mediating role of ad attitude and brand attitude, regardless of the explicitness of the message. In terms of the message format, no differences were observed.Research limitations/implications>The differential power of using celebrities across different new media to promote brands suggests the importance of interactivity in the context of celebrity endorsement. Additionally, the absence of differences in terms of message formats would show that the presence of the celebrity per se has a powerful effect.Practical implications>Firms using new media to deliver their brand communication, including celebrity endorsements, can better understand the different capabilities of social media and digital media.Originality/value>In the context in which empirical research equates new media with social media, this study provides an examination of celebrity endorsement assuming the complexity of the celebrity endorsement ion the current scenario: different types of new media and different types of message formats.